2011
DOI: 10.1007/s00792-011-0398-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial diversity in proglacial soil from Kafni Glacier, Himalayan Mountain ranges, India, with the bacterial diversity of other glaciers in the world

Abstract: Two 16S rRNA gene clone libraries (KF and KS) were constructed using two soil samples (K7s and K8s) collected near Kafni Glacier, Himalayas. The two libraries yielded a total of 648 clones. Phyla Actinobacteria, Bacteroidetes, Chloroflexi Firmicutes, Proteobacteria, Spirochaetae, Tenericutes and Verrucomicrobia were common to the two libraries. Phyla Acidobacteria, Chlamydiae and Nitrospirae were present only in KF library, whereas Lentisphaerae and TM7 were detected only in KS. In the two libraries, clones be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…2C). The presence of viable bacteria belonging to these four phyla has been widely documented in polar, non-polar and Arctic region (38,45). Bacteria from phylum Actinobacteria and Firmicutes were usually found to be pre-dominant, followed by members of the Proteobacteria and Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
“…2C). The presence of viable bacteria belonging to these four phyla has been widely documented in polar, non-polar and Arctic region (38,45). Bacteria from phylum Actinobacteria and Firmicutes were usually found to be pre-dominant, followed by members of the Proteobacteria and Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
“…The Karakoram range blocks most of the monsoon bearing clouds, making the region arid (Namgail 2009). Based on the cloning-based cultivation-independent methods Srinivas et al 2011;Kistler et al 2013), recent studies have reported the bacterial diversity of Himalayan regions. Though cloning-based cultivation-independent approaches overcome the limitations of cultivation-based methods, owing to the methodology-based bias, e.g., PCR and sequencing depth (Vaz-Moreira et al 2011), these techniques are not efficient enough to catalog the rare microbial taxons.…”
Section: Introductionmentioning
confidence: 99%
“…Although Psychrobacter species have a global distribution, they are most frequently found in cold and other non-polar environments of low water activity (Rodrigues et al, 2009). At the time of writing, the genus contained 37 species with validly published names, among which at least 18 species were isolated from low-temperature environments, including Antarctic glacier mud and sediment (Bozal et al, 2003), Antarctic ornithogenic soils (Bowman et al, 1996), sea ice (Romanenko et al, 2004), alpine soil (Srinivas et al, 2011), Siberian permafrost (Bakermans et al, 2006) and Arctic seawater (Zeng et al, 2015). In this study, we report the detailed taxonomic characterization of one Psychrobacter-like bacterial strain, BIc20019 T .…”
mentioning
confidence: 99%